PENGARUH BUDAYA KERJA, PEMBERDAYAAN DAN SIKAP KERJA TERHADAP KINERJA PEGAWAI DI BADAN KEPEGAWAIAN DAERAH KABUPATEN LABUHANBATU SELATAN - Rizki Zenia; Nazamuddin .; Dimaswari Sefrizal; Santi Akusti; Sarimin . (Jurnal Prodi Fakultas Ekonomi-UISU, 2021)
Problem of this study how influence of job culture on performance. How influence of empowerment on performance. How influence of work attitude on performance. How influence job culture, empowerment and work attitude on performance. The purpose of this study to determine and analyze the effect of job culture on performance. Determine and analyze the effect of empowerment on performance. Determine and analyze the effect of work attitude on performance. Determine and analyze the effect of job culture, empowerment and work attitude on performance. Sample in the study is 34 employees. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate job culture variable has a positive and significant effect on performance. empowerment variable has a positive and significant effect on performance. work attitude variable has a positive and significant effect on performance. Job culture, empowerment and work attitude variable has a positive and significant effect on performance.